Synthesis and Screening of Some Novel Substituted Indoles Contained Fused Triazolo[1,5-a]pyridine and Thiazolo[3,2-a]pyridine Derivatives - M. Khalifa1, Nagy; M. Naglah1, Ahmed; A. Al-Omar1, Mohamed; El-Galil E. Amr1, Abd (Asian Journal of Chemistry, 2014)
A series of heterocyclic derivatives including 1H-pyrazol-4-carbonitrile (3), 1H pyrazol-5(4H)-one (4,5), 2-thioxopyrimidine-4,6-dione (6) 1,2,4-triazole-3(4H)-one (7), 1,6-diaminopyridine (9), triazolo[1,5-a]pyridin (10) and thiazolo[3,2-a]pyridine (11) moieties conjugated with 1-substituted indole moiety were synthesized on reaction with cyanoacetohydrazide, 3-amino-5-oxo-2-pyrazoline, thiobarbituric acid, thiosemicarbazide, malononitrile followed by cyanoacetohydrazide, different aromatic aldehydes and mercaptoacetic acid, respectively, by using 1-[2-(piperidin-1-yl)ethyl]-1H-indole-3-carbaldehyde (1) as starting material. The structures of all the newly synthesized products have been established on the basis of analytical and spectral data.The antimicrobial activity of some selected products was examined and some of them showed good activities.